Factors affecting house purchase decision of middle class income in Kuantan - Norhisyam , Awang (2015)
The main purpose of the study is to investigate the effecting of key factors on housing purchase decision of middle class earner in Kuantan. First, a model which is proposed based on analyzing of previous literature. Then the model is tested on a on a larger survey of 292 samples. The study finds out a strong positive relationship between top two factors, including "affordability ownership", "location and environment" and customers' housing purchase decision. The three weaker positive relationship factors are "house feature", "developer reputation" and "family factor" to housing decision makers. It is also found that there is difference in decision making of customers according to different demographics consisting of gender, age, marital status, monthly income and education level.